Peningkatan Kapasitas Petani Melalui Pelatihan Pembuatan Pupuk Organik Bokashi di Daerah Perbatasan Darat Kalimantan Barat - Arief Sirajuddin; Kartika Ekasari; Racmat Racmat; Aminuddin Saade (DEDIKASI, 2019)
This activity was motivated by the fact that the people in Mentibar Village, Paloh Sub-district of SambasRegency are farmers who had only relied on their farming activities using of inorganic fertilizer especially Ureafertilizer from Malaysia, which the price is not cheap and sometimes the unavailable. The farmers in Mentibarvillage are new to Bokashi organic fertilizer, which its main ingredients are widely available in the village such aslivestock, fine bran, straw, etc. In this study, we conducted training and counselling to improve farmers' knowledgeand skills in making organic fertilizer. Bokashi as an alternative fertilizer can be used by farmers in their ricecultivation and at the same time to less reliant to inorganic fertilizer. The purpose of this Community Serviceactivities are: First, to increase the knowledge and skills of farmers in making Bokashi organic fertilizer. Second, toprovide an understanding that relying on inorganic fertilizer can damage the soil and produce pollution. Third,farmers will be able to utilize the materials around them to be used as Bokashi fertilizers such as livestock, bran,husks and rice straw.